Sinopse das Licopodiaceas do Brasil - Windisch, P. G.; Ollgaard, Benjamin
3 ejemplares
Keywords: Lycopodiella; Lycopodiaceae; Lycopodium; Huperzia; Argentina; Brasil; Flora; Paraguay; Helechos; Pteridofitas